Characterisation of coal & biomass mixture for co-gasifications - Nur Farah Hanim, Rahmat (2014)
Biomass fuels can be produce by widely available raw materials which is come from different sources and wide variety of forms. Co-gasification can reduce the cost of the feedstock and reduce the problems that occur in plant-operation due to the production of tar (Kumabe et al., 2006). For the pre-treatment of biomass, sample received were relatively dry for 24h under sunlight having less than 10 wt% moisture and were in the form of whole bunches. The EFB was manually chopped into small pieces. Then a grinder was used to reduce the size. For first analysis, heating value of EFB was determined by burning a weighed sample in an adiabatic oxygen-bomb calorimeter (model Parr 1341, USA). The apparent density of the EFB samples was determined using a gas pycnometer (model-. Micromeritics, AccuPyc II 1340) with helium as purging gas. The percentages of carbon, hydrogen, nitrogen, sulfur and oxygen (by difference) of the EFB sample were determined after complete combustion of the sample using a CHNS/O Analyzer (model LECO TruSpec CUN, USA) following the ASTM D-5291 method (Kezhong et al., 2009). The contents of moisture (dry basis), volatile matter, fixed carbon and ash were determined using a thermogravimetric analyzer (model Mettler Toledo, TGA/SDTA85 1, USA). One of the main objectives of this research is to study the effect on characteristic of mixture coal and biomass in co-gasification and compare with coal gasification or biomass gasification itself. For higher heating value, the average value is 24.5697 MJIkg. For apparent density of the mixture, as percentage of biomass increase, the apparent density also increased but after 70% biomass, the apparent--density starts-to reduced. For the proximate analysis, BO have 2 times greater weight loss compared to BlOO at the same temperature. For elemental analysis, B100 contains 2 times greater oxygen compared to BO but have greater carbon number compared to B100.Unlike coal, biomass with low ash and sulphur content, a high volatile matter yield and- fixed carbon with high reactivity could potentially be attractive from the economic, environmental and social points of view that poor coal. Low density and low calorific value of biomass causes an increase in the cost of transportation and storage, hence by co-gasification of biomass with coal is more economical compared to biomass alone.